Libertad de expresión visión de los comunicadores en la prensa escrita Babahoyo 2019 - Carpio Cerna, Cynthia Cecibel (2020)
In the present case study, the limit of freedom of expression will be analyzed and if it is restricted or not in the country, mainly in the city of Babahoyo, it is for this reason that a type of descriptive and explanatory research is used, where will proceed to conduct interviews with two journalists from the local media, in order to know the reality of freedom of expression in the journalistic environment. Once the interviews were carried out, it was known that freedom of expression is an intangible right of the human being, but that it is regulated for public expression by the Organic Law of Communication, which requires social communicators and reporters to perform a field investigation with the purpose of gathering the necessary facts to be able to publish a story, but what happens if the sources do not want to corroborate the facts, or have been limited by regulatory bodies or higher in order to limit free expression, is precisely this question is raised as a question to know and inquire if there is a true free expression in the country and specifically in the canton.